Defect‐Rich Co−CoOx‐Graphene Nanocatalysts for Efficient Hydrogen Production from Ammonia Borane. Issue 19 (4th September 2020) - Guan, Shuyan; Zhang, Lina; Zhang, Huanhuan; Guo, Yong; Liu, Baozhong; Wen, Hao; Fan, Yanping; Li, Baojun
Abstract: Chemical hydrogen storage ammonia borane has attracted extensive attention as a method of efficient utilization of hydrogen energy. The high‐efficiency catalysts are the main factor restricting the hydrogen production of ammonia borane. In this paper, the synergistic effect of Co and CoOx supported on graphene (named Co−CoOx @GO‐II) promotes the efficient hydrogen production of ammonia borane, and its catalytic hydrogen production rate can reach 5813 mL min −1 gCo −1 at 298 K, the corresponding TOF is 15.33 min −1 . After five stability tests, Co−CoOx @GO‐II maintained 65% of its original catalytic performance. The synergy of metal and metal oxide and the defects in the atomic arrangement ensure the catalytic activity, the large specific surface area of graphene ensures the dispersion and fixation. This strategy may provide a possibility to design high‐performance transition metal catalysts. Abstract : Synergistic effect of Co and CoOx supported on graphene (named Co−CoOx @GO‐II) promotes the efficient hydrogen production of ammonia borane, and its catalytic hydrogen production rate can reach 5813 mL min −1 gCo −1 at 298 K, the corresponding TOF is 15.33 min −1 . After five stability tests, Co−CoOx @GO‐II maintained 65% of its original catalytic performance.